Resident and supervisor perceptions of gaining obstetrical competency in Family Medicine: a qualitative descriptive study - Arora, Nisha; Koppula, Sudha; Brown, Judith (Canadian Medical Education Journal, 2024)
Introduction: Canadian Family Medicine (FM) residents, upon graduation, are disinclined to provide intrapartum care. The FM resident experience with obstetrical training has not been studied in over a decade while the FM landscape has changed. This study explored the FM resident experience in working towards their obstetrical competencies as one of the chief influences on their career decision to provide intrapartum care or not. Methods: Using a qualitative descriptive design, we conducted semi-structured interviews with second-year FM residents (n = 7) and obstetrical supervisors (n = 8) from one Ontario FM program. We coded and interpreted the transcripts for common themes. Results: FM residents working towards their intrapartum skills are influenced by the following themes: the learners’ unique and individual experience and expectations; opportunities in the training environment; and learning obstetrics in the changing FM landscape. Notably, the influence of FM maternity care role models permeated all themes. Conclusion: This study offers insight into potential areas of intervention to improve the FM residency training experience in intrapartum care. Investment in FM maternity education, in the undergraduate and postgraduate medical curricula, with continued support in practice, is critical to maintain comprehensive education and patient care, especially while Canada faces a maternity care crisis.